Analisis keuntungan pelaku usaha kerang kalandue (Polymesoda erosa) pada ekosistem mangrove di Kelurahan Korumba Kecamatan Mandonga Kota Kendari - Firdaus; Nurdiana A; Piliana, Wa Ode; Rosmawati; La Ola, La Onu; Patiung, Seventry Meliana (Universitas Halu Oleo, 2023)
This study aims to determine the total costs, revenues, and profits of mangrove clams (Polymesoda erosa) fisheries in mangrove ecosystems. This research was carried out in April 2022 in Korumba Village, Mandonga District, Kendari City. The sampling method used was the census method with the number of respondents being 8 mangrove clam fishermen. Data collection was carried out through interviews, observation and documentation. The data analysis used was cost, revenue and profit analysis. The study showed that the husband caught shellfish whereas the fisherman's wife was responsible for selling the clams. A small portion of the catch was taken for personal consumption and most was for sale. The average number of clams caught per month was 276 kg. The results of the analysis showed that the average total cost per month was IDR 488,150. The average amount of income per month was IDR 1,381,875. The average profit per month was IDR 876,100. This study indicated that mangrove clams fisheries in the mangrove ecosystem of Korumba Village, Mandonga District, Kendari City are profitable.